2001
DOI: 10.1038/sj.gt.3301474
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface display of a lysosomal enzyme for extracellular gene-directed enzyme prodrug therapy

Abstract: Prodrug conversion is a promising approach to cytotoxic gene therapy if an efficient transfer of the generated drug to adjacent cells can be achieved. To maximize the efficacy of this strategy we sought to develop a system that is based on a human enzyme, acts extracellularly yet in close vicinity of the transduced cell and can be used with multiple prodrugs. Results obtained with a secreted version of human ␤-glucuronidase suggested that this enzyme could be a suitable candidate, although a more stringent ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…34 Similarly, Brusselbach et al demonstrated that cell surface display of hbG for extracellular gene-directed enzyme prodrug therapy can produce strong bystander killing and potent antitumor activity. 36 We recently demonstrated that mbG expressed on tumor cells effectively activated a glucuronide prodrug and produced tumor regressions in a mouse model. 37 bG is therefore an attractive enzyme for specific conversion of glucuronide prodrugs for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…34 Similarly, Brusselbach et al demonstrated that cell surface display of hbG for extracellular gene-directed enzyme prodrug therapy can produce strong bystander killing and potent antitumor activity. 36 We recently demonstrated that mbG expressed on tumor cells effectively activated a glucuronide prodrug and produced tumor regressions in a mouse model. 37 bG is therefore an attractive enzyme for specific conversion of glucuronide prodrugs for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, secreted enzymes might leak away from the site of the tumour. Therefore, cell surface-tethered forms of prodrugconverting enzymes, such as b-glucuronidase or carboxypeptidase G2, were developed to prevent leakage of untargeted enzyme from the tumour, while prodrug activation is retained (Spooner et al, 2000;Heine et al, 2001). Another way to prevent diffusion of the enzyme from the tumour is secretion by transduced tumour cells of a fusion protein consisting of an scFv antibody and a prodrugconverting enzyme, which can subsequently bind to tumour cells Oosterhoff et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Given the fact that current gene transfer technologies do not allow transduction of all tumour cells, a bystander effect is warranted to achieve effective kill of untransduced tumour cells. To improve the bystander effect of adenoviral vector-mediated GDEPT approaches, secreted and surface-tethered prodrug-converting enzymes have been investigated (Spooner et al, 2000;Weyel et al, 2000;Heine et al, 2001;Oosterhoff et al, 2003). We envisioned that a targeted, secreted form of CE2, consisting of the secreted form of CE2 (sCE2) fused to a tumour-specific scFv antibody would provide an enlarged bystander effect and would furthermore theoretically prevent leakage of the protein into the circulation, thereby reducing systemic side effects.…”
mentioning
confidence: 99%
“…The solution to this problem could be secretion of a targeted form or a surface tethered form of GUSh by transduced tumour cells, as it might result in retention of the enzyme within the tumour. Recently, a surface tethered form of GUSh has been constructed by fusion of the transmembrane domain of the human PDGF receptor to a C-terminally truncated form of GUSh (Heine et al, 2001). This GDEPT system has been shown to produce a potent anti-tumour effect in vivo.…”
Section: Experimental Therapeuticsmentioning
confidence: 99%